Different storage conditions and 1-methylcyclopropyl in pitaya post-harvest conservation (Revista de Ciências Agroveterinárias, 2023)
Fast perishability of dragon fruit requires that strategies be adopted to extend its post-harvest shelf life, in order to reduce losses, maintain quality and increase the financial return of economic activity. The objective of this work was to evaluate the effect of storage conditions in combination with the application of 1-methylcyclopropene (1-MCP) on the quality maintenance of red dragon fruit. The treatments evaluated were cold storage (CS; 21 kPa O2 + 0.03 kPa CO2), controlled atmosphere (CA; 2 kPa O2 + 5 kPa CO2) and modified atmosphere (MA; 40 µm thick low-density polyethylene bags) combined or not with the application of 1-MCP (300 nL.L-1), with four replications per treatment. The fruits of all treatments were stored for 20 days at 13 ± 2°C and relative humidity (RH) of 90 ± 5%, followed by 3 days of exposure at ambient conditions (20 ± 3°C and RH of 70 ± 5%). After the shelf life, CA and MA maintained fruits with a higher hue angle. The treatment of 1-MPC added to CA and MA provided greater force for pulp penetration. CS, AC and MA, added to the treatment with 1-MCP, are promising technologies to be used in the storage of dragon fruit.
Keywords: Hylocereus undatus; dragon fruit; controlled atmosphere; modified atmosphere; crops, agricultural; fruit; product storage